Pemanfaatan Sampah Plastik Menjadi Tikar Piknik - Siti Roudhlotul Hikamah; Haning Hasbiyati; Wardah; Ifadatul Afrah; Bilal Karomah (BADAN PENERBIT STIEPARI PRESS, 2024)
Plastic waste is a type of waste that is difficult to break down properly. Community support is needed to re-manage plastic waste in the form of useful products, namely by turning it into picnic mats. This is aimed at helping to improve of the people of Pelalangan Hamlet, Karang Kedawung Village, Jember Regency regarding recycling plastic waste properly, and provide understanding to the community about the use of inorganic waste. The method that will be used is the Asset Based Community Development method activities in the use of plastic waste into picnic mats.